Violation of Moral Values as Seen in Shawâs The Doctorâs Dilemma - , AMARYLIANI SUKMA GUSTARIANA; , Dra. Esmeraldayanti Sosronegoro, SU. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Doctorâs Dilemma is a play written by Bernard Shaw, known as tragic play which has become a success and has been reproduced several times. This play has moral values concealed within it. This study aims to find out the moral actions, the reason for Bernard Shawâs skeptical perception towards physicians, and to learn the circumstances of medical treatment in the early 20th century in England by analyzing the preface, dialogues, and stage directions in the play. This study basically adopts a combination between mimetic and expressive approach which regards The Doctorâs Dilemma as the expression of Shawâs idea and portraits of medical and social life in early 20th century. The analysis is focused on the violation of medical ethics and social norms because they are the dominant in the play. The results of the analysis are the failure of the physician characters in the play to keep their oath as medical attendants because they violate five from eight points of their general duties based on the medical ethic. Then, it is also found out that several characters do not obey the social norm, such as being dishonest, and doing some actions to pursue their personal benefits.